2021
DOI: 10.1038/s41467-021-22293-y
|View full text |Cite
|
Sign up to set email alerts
|

A designer FG-Nup that reconstitutes the selective transport barrier of the nuclear pore complex

Abstract: Nuclear Pore Complexes (NPCs) regulate bidirectional transport between the nucleus and the cytoplasm. Intrinsically disordered FG-Nups line the NPC lumen and form a selective barrier, where transport of most proteins is inhibited whereas specific transporter proteins freely pass. The mechanism underlying selective transport through the NPC is still debated. Here, we reconstitute the selective behaviour of the NPC bottom-up by introducing a rationally designed artificial FG-Nup that mimics natural Nups. Using Q… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 78 publications
5
55
1
Order By: Relevance
“…NPCs control the movement of various proteins or biomolecules in and out of the nucleus based on the size 46 . This size-selective transport of large molecules through NPC were reported earlier 47,48 . The knowledge of the functioning and transport mechanism of the particles through the membrane channels like NPC has implications in cellular processes.…”
Section: Introductionsupporting
confidence: 82%
“…NPCs control the movement of various proteins or biomolecules in and out of the nucleus based on the size 46 . This size-selective transport of large molecules through NPC were reported earlier 47,48 . The knowledge of the functioning and transport mechanism of the particles through the membrane channels like NPC has implications in cellular processes.…”
Section: Introductionsupporting
confidence: 82%
“…Our bioinformatic analysis revealed that all orthologs of the NUP58 protein are also potential amyloids. We have also found a fragment which is amyloidogenic in many orthologs and located outside of the FG repeat region, which is supposed to play a key role in formation of selective barrier [40][41][42]. Notably, the conservation of the protein sequence in this fragment is lower than the conservation of amyloidogenic properties (Figure 1b).…”
Section: Human Nup58 Protein Demonstrates Amyloid Properties In C-dag Systemmentioning
confidence: 90%
“…However, there is no ultrastructural evidence for a pore-associated structure at the nucleomorph membrane and the retention of these subunits may indicate recruitment to other processes. Secondly, attempts to create an artificial pore, using truncated versions of yeast Nsp1 and Nup100 [ 185 ] or a designer ‘NupX’ [ 186 ], produced pores with selective permeability, suggesting minimal requirements to achieve gating. A self-assembling pore of just two POMs, Ndc1 and an FG-containing Pom121 in a lipid bilayer has also been achieved [ 187 ].…”
Section: Npc Evolution: a Minimal Pore?mentioning
confidence: 99%